Different configurations of transferred atmospheric pressure plasma jet and their application to polymer treatment - Nascimento, Fellype do[UNESP]; Quade, Antje; Canesqui, Mara Adriana; Kostov, Konstantin Georgiev [UNESP] (Wiley, 2023)
The employment of atmospheric pressure plasma jets (APPJs) in a large sort of applications is limited by the adversities related to the size of the treated area and the difficulty to reach the target. The use of devices that employ long tubes in their structure has contributed significantly to overcome these challenges. In this work, two different plasma systems employing the jet transfer technique are compared. The main difference between the two devices is how the long plastic tube was assembled. The first one uses a copper wire placed inside a long plastic tube. The other device has a metallic mesh installed in a concentric arrangement between two coaxial plastic tubes. As a result, the two APPJ systems exhibit different properties, with the wire assembly being more powerful, also presenting higher values for the electrical current and rotational temperature when compared to the mesh mounting. X-ray photoelectron spectroscopy (XPS) demonstrates that both configurations were capable of inserting O-containing functional groups on the polypropylene (PP) surface. However, the transferred plasma jet with wire assembly was able to add more functional groups on the PP surface. The results from XPS analysis were corroborated with water contact angle measurements (WCA), being that lower WCA values were obtained when the PP surface presented higher amounts of O-containing groups. Furthermore, the results suggest that the APPJ with wire configuration is more appropriate for material treatments, while the transferred jet with mesh arrangement tends to present lower electrical current values, being more suitable for biological applications.
Keywords: DBD plasma; plasma jets; plasma properties; plasma treatment; transferred plasma